2011
DOI: 10.1021/nn2005393
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Contact-Angle Hysteresis for Droplets on Nanopillared Surface and in the Cassie and Wenzel States: A Molecular Dynamics Simulation Study

Abstract: We perform large-scale molecular dynamics simulations to measure the contact-angle hysteresis for a nanodroplet of water placed on a nanopillared surface. The water droplet can be in either the Cassie state (droplet being on top of the nanopillared surface) or the Wenzel state (droplet being in contact with the bottom of nanopillar grooves). To measure the contact-angle hysteresis in a quantitative fashion, the molecular dynamics simulation is designed such that the number of water molecules in the droplets ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 28 publications
3
111
0
Order By: Relevance
“…It can be observed that the variation of the CA for different droplet sizes is <3°. These results are consistent with MD results of water droplet containing 12,000-100,000 molecules placed on nanopillared surfaces [27]. Thus, we concluded that the line tension effect was limited for the droplet we studied.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It can be observed that the variation of the CA for different droplet sizes is <3°. These results are consistent with MD results of water droplet containing 12,000-100,000 molecules placed on nanopillared surfaces [27]. Thus, we concluded that the line tension effect was limited for the droplet we studied.…”
Section: Resultssupporting
confidence: 92%
“…1 Sources (a-e) and some influencing factors (f-g) of the CAH significant. As far as we are aware, there are only a few studies which have reported the investigation of CAH of nanodroplets using molecular dynamics (MD) simulations [26,27]. Hong and coworkers studied the static and dynamic CAs of water droplets on solid surfaces of different surface energies [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the nanostructures (particularly the conical protuberances in Fig. 1B) also minimize the contact area and therefore adhesive forces between the particle and the superhydrophobic surface (11,13), which is corroborated by the small contact angle hysteresis associated with fine textures (34)(35)(36). As a proof of concept, the jumping-condensate selfcleaning was achieved on nanostructured copper surfaces prepared following ref.…”
Section: Discussionmentioning
confidence: 65%
“…Koishi et al [11] simulated a large scale transition between Wenzel State and Cassie State on hydrophobic surface. They also investigated the contact angle hysteresis for droplets on nanopillared surface [12] . Vrancken et al…”
Section: Background and Literature Reviewmentioning
confidence: 99%